2008
DOI: 10.1002/jmv.21225
|View full text |Cite
|
Sign up to set email alerts
|

Virus load dynamics of individual CMV‐genotypes in lung transplant recipients with mixed‐genotype infections

Abstract: Human cytomegalovirus (CMV) is a major cause of disease and transplant dysfunction in lung transplant recipients. Simultaneous emergence of more than one CMV-genotype can occur, and appears to be disadvantageous for the patient. In this study, the dynamics of individual CMV-genotypes in blood and lung was assessed within mixed CMV-genotype populations emerging after lung transplantation. In 69 plasma and 76 bronchoalveolar lavage samples of 16 lung transplant recipients with mixed CMV-genotype infections withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
42
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 29 publications
4
42
0
Order By: Relevance
“…For this test, HCMV DNA was isolated directly from patient samples using a QIAamp RNA isolation kit (Qiagen, Hilden, Germany). Samples with a viral DNA load of at least 5 ϫ 10 4 copies/ml were then tested using gB and gH genotype-specific quantitative PCR assays, which have been described previously (14), to preselect clinical samples with mixed HCMV infections.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this test, HCMV DNA was isolated directly from patient samples using a QIAamp RNA isolation kit (Qiagen, Hilden, Germany). Samples with a viral DNA load of at least 5 ϫ 10 4 copies/ml were then tested using gB and gH genotype-specific quantitative PCR assays, which have been described previously (14), to preselect clinical samples with mixed HCMV infections.…”
Section: Methodsmentioning
confidence: 99%
“…Even cloning of PCR products and subsequent Sanger sequencing do not allow a sensitive assessment of the genotypes present unless an extremely large number of individual clones is sequenced. Improved genotype-specific real-time-PCR-based assays have been established recently for gB and gH genotyping, and these allow simultaneous detection and quantitation of distinct genotypes in mixed infections down to a level of 5% or even less (14,28).In the present study, we determined the relative amounts of different HCMV genotypes in clinical samples from lung transplant patients by using the highly sensitive ultradeep-pyrosequencing (UDPS) technology. UDPS genotyping of three of the most variable genes within the HCMV genome, the gN, gO, and UL139 genes, revealed that there is a substantially higher diversity of HCMV genotype populations in patients with mixed HCMV infection than has been recognized previously and that the HCMV strains show a distinct pattern in…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Active HHV-6B infection generally occurs only once throughout life (at the time of the primary infection) in immunocompetent individuals, but it may occur several times in transplant recipients (8) or DIHS patients (17). Frequent HHV-6B reactivation, as evidenced by the repeated isolation of the virus during an active viral infection, was observed in hematopoietic stem cell transplant (HSCT) recipients (8, 18).Previous reports detected mixed infections with multiple cytomegalovirus (CMV) strains in the same human herpesvirus subfamily (Betaherpesvirinae subfamily) as HHV-6B in a variety of patient populations, including immunocompetent and immunocompromised patients (19)(20)(21)(22). Furthermore, other studies have suggested that the genotype of the virus may be associated with the severity of the congenital cytomegalovirus infection (23).…”
mentioning
confidence: 99%
“…Previous reports detected mixed infections with multiple cytomegalovirus (CMV) strains in the same human herpesvirus subfamily (Betaherpesvirinae subfamily) as HHV-6B in a variety of patient populations, including immunocompetent and immunocompromised patients (19)(20)(21)(22). Furthermore, other studies have suggested that the genotype of the virus may be associated with the severity of the congenital cytomegalovirus infection (23).…”
mentioning
confidence: 99%